AB0289 EFFICACY, SAFETY AND IMMUNOGENICITY IN PATIENTS WITH RHEUMATOID ARTHRITIS COMPARING PF-06410293 (ADL-PF), AN ADALIMUMAB (ADL) BIOSIMILAR, AND REFERENCE ADL: RESULTS FROM WEEK 26–52 OF A DOUBLE-BLIND, RANDOMISED PHASE 3 STUDY INCLUDING PATIENTS WHO SWITCHED FROM ADL-PF TO REFERENCE ADL AT WEEK 26. (2nd June 2020) - Fleischmann, R.; Alvarez, D.; Bock, A.; Cronenberger, C.; Vranic, I.; Zhang, W.; Alten, R.
Abstract : Background: PF-06410293 (ADL-PF) is an adalimumab biosimilar approved for the treatment of several inflammatory and autoimmune indications. 1 The efficacy, safety and immunogenicity of ADL-PF and reference adalimumab sourced from the European Union (ADL-EU) in patients with rheumatoid arthritis (RA) have been demonstrated to be similar in a randomised controlled trial up to 26 weeks (wks; treatment period 1 [TP1]). 2 Objectives: To evaluate the efficacy, safety and immunogenicity of ADL-PF and ADL-EU in patients with moderate to severe RA on longer-term treatment, and following a treatment switch from ADL-EU to ADL-PF in a subset of patients. Methods: This multinational, randomised, double-blind, parallel-group study compared ADL-PF and ADL-EU in essentially biologic-naïve patients with active RA despite methotrexate (MTX) (NCT02480153 ). In TP1, patients were randomised (1:1) to ADL-PF or ADL-EU (40 mg subcutaneous injection every 2 wks) for 26 wks while continuing MTX (10–25 mg/wk). The primary endpoint was achievement of American College of Rheumatology response (ACR20) at Wk 12. At Wk 26, the start of treatment period 2 (TP2), patients receiving ADL-EU were blindly re-randomised (1:1) to remain on ADL-EU or switch to ADL-PF for 26 wks while patients receiving ADL-PF continued treatment in a blinded manner. Secondary efficacy endpoints at Wks 26, 30, 36, 44 and 52 (ACR20/50/70, European League Against Rheumatism [EULAR] response, Disease Activity Score [DAS] 28-4[CRP] <2.6 and ACR/EULAR defined remission), safety events and percentage of patients with anti-drug antibodies (ADA) were assessed. Results: In TP1, 597 patients were randomised to ADL-PF (n=297) or ADL-EU (n=300). At Wk 26, 552 patients were re-randomised for TP2 (continued ADL-PF, n=283; continued ADL-EU, n=135; switched from ADL-EU to ADL-PF, n=134). Patients who demonstrated at least minimal efficacy continued in TP2. Observed ACR20 rates were comparable between treatment groups at all visits during TP2 (Figure ). Other measures of deep response (ACR70, EULAR good response, DAS28-4(CRP) <2.6 and ACR/EULAR defined remission) showed maintained efficacy during TP2 in all treatment groups. Incidences of treatment-emergent adverse events were comparable between treatment groups (Table ). Overall, incidences of ADA through Wk 52 were comparable between treatment groups (47.3%, 54.1% and 45.9% for patients who continued ADL-PF, continued ADL-EU or switched from ADL-EU to ADL-PF, respectively). In patients who switched from ADL-EU to ADL-PF compared with patients who continued ADL-EU, the increase in ADA incidence over TP2 was 0.8% (from 45.1% to 45.9%) versus 6.7% (from 47.4% to 54.1%), respectively. Conclusion: TP2 results demonstrated comparable efficacy, safety and immunogenicity between ADL-PF and ADL-EU was maintained up to Wk 56 and was unaffected by a blinded switch from ADL-EU to ADL-PF at Wk 26. References: [1]Pfizer Inc, 2019. http://labeling.pfizer.com/ShowLabeling.aspx?id=12780 [2]Fleischmann RM et al, Arthritis Res Ther 2018;20:178. Acknowledgments: Medical writing support, provided by Jacqui Oliver of Engage Scientific Solutions. The study was funded by Pfizer. Disclosure of Interests: Roy Fleischmann Grant/research support from: AbbVie, Akros, Amgen, AstraZeneca, Bristol-Myers Squibb, Boehringer, IngelhCentrexion, Eli Lilly, EMD Serono, Genentech, Gilead, Janssen, Merck, Nektar, Novartis, Pfizer, Regeneron Pharmaceuticals, Inc., Roche, Samsung, Sandoz, Sanofi Genzyme, Selecta, Taiho, UCB, Consultant of: AbbVie, ACEA, Amgen, Bristol-Myers Squibb, Eli Lilly, Gilead, GlaxoSmithKline, Novartis, Pfizer, Sanofi Genzyme, UCB, Daniel Alvarez Shareholder of: Pfizer, Employee of: Pfizer, Amy Bock Shareholder of: Pfizer, Employee of: Pfizer, Carol Cronenberger Shareholder of: Pfizer, Employee of: Pfizer, Ivana Vranic Shareholder of: Pfizer, Employee of: Pfizer, Wuyan Zhang Shareholder of: Pfizer, Employee of: Pfizer, Rieke Alten Grant/research support from: Pfizer, Galapagos, Galapagos NV, Gilead, Gilead Sciences, Inc., Novartis, Consultant of: Pfizer, Speakers bureau: Pfizer